2022
DOI: 10.47203/ijch.2022.v34i02.021
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of Depression, Anxiety and Stress among Nursing Students

Abstract: Background: Nursing students experience significant amount of depression, anxiety and stress throughout their undergraduate education and there is limited evidence regarding magnitude of depression, anxiety and stress among them in India. Aims & Objectives: To assess the prevalence of depression, anxiety and stress and associated factors among nursing students. Materials & Methods: A web based cross sectional study was conducted among 214 nursing students of B.Sc. Nursing College, Dibrugarh in May 2021… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…By (Prasetyaningsih et al, 2021) states that stress and anxiety can contribute to the development of gastritis. Anxiety experienced by students is related to conflicts with friends, breaking up with loved ones, selecting supervisors, satisfaction with the nursing profession, fear of failing in examinations, increased class workload, and fewer holidays (Baruah et al, 2022). When students experience psychological disorders, hormonal and immune disorders will be in the body, making students susceptible to gastritis.…”
Section: Resultsmentioning
confidence: 99%
“…By (Prasetyaningsih et al, 2021) states that stress and anxiety can contribute to the development of gastritis. Anxiety experienced by students is related to conflicts with friends, breaking up with loved ones, selecting supervisors, satisfaction with the nursing profession, fear of failing in examinations, increased class workload, and fewer holidays (Baruah et al, 2022). When students experience psychological disorders, hormonal and immune disorders will be in the body, making students susceptible to gastritis.…”
Section: Resultsmentioning
confidence: 99%
“…4 One study cited exam failures, vaccination status, course selection, and the nursing profession in general caused depression in nursing students. 5 Other research found that nursing student stress after the COVID-19 pandemic stemmed from classroom and clinical learning environment changes, fear of the unknown, and outside pressures of people discouraging them from completing the nursing program. 6 One evolving way to treat this reported depression and anxiety is the use of medical marijuana.…”
mentioning
confidence: 99%
“…Responses to the COVID-19 pandemic have induced social isolation, which increased psychological disorders such as panic disorders, anxiety, and depression in nursing students 4. One study cited exam failures, vaccination status, course selection, and the nursing profession in general caused depression in nursing students 5. Other research found that nursing student stress after the COVID-19 pandemic stemmed from classroom and clinical learning environment changes, fear of the unknown, and outside pressures of people discouraging them from completing the nursing program 6…”
mentioning
confidence: 99%